Direction of Trade Statistics : March 2018. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2018)
This quarterly issue of Direction of Trade Statistics (DOTS) provides tables with current reported data (or estimates) on the value of merchandise trade statistics (exports and imports) by partner country for all IMF member states and other nonmember countries. Summary tables are also presented for the world and major areas. DOTS republish monthly, quarterly, and annual trade statistics as submitted by countries to the IMF. Furthermore, reported data are supplemented by estimates whenever such data are not current or are not available on a monthly basis. Monthly estimates are consistent with quarterly and annual reported data, when available. The quarterly issues (DOTSQ) and the yearbook (DOTSY) present figures for the most recent quarters and years, respectively. Estimation occurs if a reporting country does not report trade with its partners for a specific period. Data are estimated for all partners. In the absence of some or all the monthly DOTS, quarterly or annual reported DOTS are used.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet